Idiomarina mangrovi sp. nov., isolated from rhizosphere soil of a mangrove Avicennia marina forest. Issue 6 (3rd April 2019) - Chen, Can; Han, Shuaibo; Zhu, Zhimin; Fu, Geyi; Wang, Ruijun; Zhang, Qin; Ye, Yanghui; Ren, Yanhu; Yan, Cen; Xu, Lin; Wu, Min
Abstract : A Gram-staining negative, aerobic, motile and rod-shaped bacterium, designated ZQ330 T, was isolated from rhizosphere soil of a mangrove ( Avicennia marina ) forest of Zhangzhou, Fujian Province, China. The growth range of NaCl concentration was 0.5–10.0 % (w/v), with an optimum at 2.5–3.0 % (w/v), the temperature range for growth was 10–40 °C, with an optimum at 28–30 °C, the pH range for growth was pH 6.0–9.5, with an optimum at pH 7.5. Phylogenetic analysis based on 16S rRNA gene sequences revealed that strain ZQ330 T exhibited less than 97.0 % sequence similarity to all type strains with validly published names and revealed that strain ZQ330 T formed a distinct lineage in the genus Idiomarina . The average nucleotide identity, and in silico DNA–DNA hybridization values between strain ZQ330 T and the reference strains were 64.8–69.9 % and 27.5–28.4 %, respectively. Chemotaxonomic analysis indicated that the main respiratory quinone was Q-8, the predominant cellular fatty acids were iso-C15 : 0, iso-C17 : 0, summed feature 9 (C16 : 0 10-methyl and/or iso-C17 : 1 ω 9c ), iso-C15 : 1 F, C16 : 0, C18 : 0, summed feature 3 (C16 : 1 ω 8c and/or iso-C16 : 1 2-OH) and summed feature 8 (C18 : 1 ω6 c and/or C18 : 1 ω7 c ). The polar lipid profile was composed of diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol, an unidentified glycolipid, an unidentified aminolipid, an unidentified phospholipid and two unidentified lipids. Based on the genotypic, phenotypic, chemotaxonomic and phylogenetic features, strain ZQ330 T is considered to represent a novel species, for which the name Idiomarina mangrovi sp. nov. is proposed. The type strain is ZQ330 T (=MCCC 1K03495 T =KCTC 62455 T ).